A case study in formal product semantics. (28th January 2008) - Feijs, Loe; Meinel, Frithjof
In an earlier work we developed a formal framework for product semantics (Feijs and Meinel, 2005). The framework borrows ideas and concepts from semiotics, i.e. the general theory of signs, and from denotational semantics, which is a branch of computer science studying the meanings of computer-related artefacts, such as programmes. So far only one case study was done using the framework. In the present article we apply the theory through another case study. The case study is about a special chair designed by Meinel, a design that was guided by sustainability concerns. The chair was not designed with a formal framework in mind but it is analysed in retrospect with the help of the original designer. The case study is not only interesting because of the chair, but it also shows the strengths and weaknesses of the formal model. It is also helpful to identify options for future work.